PRIMARY ALDOSTERONISM: THE RESULTS OF THE TREATMENT ACCORDING TO THE DATA OF RENAL ARTERIES DUPLEX SCANNING (World Science, 2019)
In the structure of arterial hypertension, primary aldosteronism (РА) ranges from 5 to 15%. Changes in intrarenal hemodynamics are due to both high blood pressure and direct aldosterone level. The purpose of the study was to analyze the results of PA treatment according to ultrasound doppler scanning of renal arteries. In general, 55 patients with PA were treated. Renal arteries duplex scanning before and after the treatment was performed in 20 patients. During treatment, the normalization of Vps, Ved, S/D, PI, PI, AT, TAMX indices was recorded in patients. The RI of the interlobar arteries slightly increased, however, it remained within the reference range. The reduction of aldosterone levels led to increase of TAMX index at the level of the renal artery trunk, S/D, RI and decrease in AT at the level of the segmental arteries, as well as increase of Ved and S/D at the level of the interlobar arteries.